Sifat Pragmatis Partikel Lah dalam Kalimat Perintah - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The study of the use of particles “lah” in command phrases in some references is always "claimed" is the result of linguistic (theory) application, the field of syntax. Actually, the  results of the existing study is in line with the application of (theory) pragmatic, because it has been determined on the “lah” function/role in the sentence. Therefore, the objectives addressed in this article are: trying to prove that the results of an existing study are implicitly a pragmatic (theory) application. Such proof has never been done, so it is interesting to discuss.The application of the review method departs on the linguistic research implementation, which is fundamental to three strategic stages: data provision, data classification and analysis, and report preparation.The evidence of the result of an existing study implicitly by applying (theory) pragmatics, the presence of  “lah” particles in the sentence is said to function / act as: 1. affirmation, 2. refiners, 3. focusing, 4. politeness, and 5. topikalisasi (command sentence).